PRE-WEANING PROGENY PERFORMANCE OF ELITE DECCANI RAMS UNDER FIELD CONDITION (Indian Journal of Animal Production and Management, 2013)
The data on pre-weaning body weights and measurements of 1641 Deccani lambs generated in the field with the use of elite selected rams were recorded. The least squares means of body weights and measurements viz. height, length and girth of lambs at birth and weaning age (3 months) were worked out. The overall mean birth weight and 3 months weights of Deccani lambs were 3.58±0.02 kg and 15.82±0.15 kg. The mean height, length and girth of lambs at birth and 3 months of age were 37.35±0.11, 35.98±0.10 and 41.23±0.11 and 48.45±0.32, 47.13±0.27 and 57.17±0.29 cm respectively. The season of birth and sex effects were significant (P
Keywords: Pre-weaning; growth; Deccani; field